Nonparametric identification of auction models with non-separable unobserved heterogeneity - Yingyao Hu; David McAdams; Matthew Shum (Centre for Microdata Methods and Practice (cemmap), 2009)
We propose a novel methodology for nonparametric identification of first-price auction models with independent private values, which accommodates auction-specific unobserved heterogeneity and bidder asymmetries, based on recent results from the econometric literature on nonclassical measurement error in Hu and Schennach (2008). Unlike Krasnokutskaya (2009), we do not require that equilibrium bids scale with the unobserved heterogeneity. Our approach accommodates a wide variety of applications, including settings in which there is an unobserved reserve price, an unobserved cost of bidding, or an unobserved number of bidders, as well as those in which the econometrician fails to observe some factor with a non-multiplicative effect on bidder values.
Keywords: 330; Auktion; Statistischer Fehler; Nichtparametrisches Verfahren